2023
DOI: 10.1111/1365-2745.14184
|View full text |Cite
|
Sign up to set email alerts
|

Competition‐induced tree mortality across Europe is driven by shade tolerance, proportion of conspecifics and drought

Niko Kulha,
Juha Honkaniemi,
Julien Barrere
et al.

Abstract: Forest stand densities are increasing in the boreal and temperate biomes, suggesting that tree‐tree competition is intensifying. Anticipating the consequences of this intensified competition is difficult because competition‐induced mortality may depend not only on the occurrence of extreme climatic events such as drought, but also on stand composition, since tree species differ in their ability to compete and tolerate competition. A better understanding of the effects of stand composition and drought on compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 119 publications
1
3
0
Order By: Relevance
“…This finding contradicts predictions of the SGH (Bertness & Callaway, 1994) and contributes to an increasing body of evidence that in severely water-limited environments, plant-plant interactions often become increasingly competitive, rather than facilitative (Barron-Gafford et al, 2017;Maestre & Cortina, 2004;O'Brien et al, 2017;Tielbörger & Kadmon, 2000). Further, our finding that stronger competition was associated with reduced precipitation is supported by previous similar studies that assess how temporal variation in rainfall determines the nature of plant-plant interactions (Diez et al, 2021;Tielbörger & Kadmon, 2000) and by a recent study that found drought tended to increase competition-induced tree mortality across parts of Europe (Kulha et al, 2023). Stronger competition in dry conditions has important implications for tree F I G U R E 1 Partial residual plots depicting the relationship between (a) Eucalyptus delegatensis and (b) Eucalyptus regnans annual absolute basal area increment (BAI) (cm 2 ) and neighbourhood metrics (NMs) (community-and functional group-level neighbourhood basal area; cm 2 ) in three sampling periods with different climatic conditions.…”
Section: Discussionsupporting
confidence: 84%
“…This finding contradicts predictions of the SGH (Bertness & Callaway, 1994) and contributes to an increasing body of evidence that in severely water-limited environments, plant-plant interactions often become increasingly competitive, rather than facilitative (Barron-Gafford et al, 2017;Maestre & Cortina, 2004;O'Brien et al, 2017;Tielbörger & Kadmon, 2000). Further, our finding that stronger competition was associated with reduced precipitation is supported by previous similar studies that assess how temporal variation in rainfall determines the nature of plant-plant interactions (Diez et al, 2021;Tielbörger & Kadmon, 2000) and by a recent study that found drought tended to increase competition-induced tree mortality across parts of Europe (Kulha et al, 2023). Stronger competition in dry conditions has important implications for tree F I G U R E 1 Partial residual plots depicting the relationship between (a) Eucalyptus delegatensis and (b) Eucalyptus regnans annual absolute basal area increment (BAI) (cm 2 ) and neighbourhood metrics (NMs) (community-and functional group-level neighbourhood basal area; cm 2 ) in three sampling periods with different climatic conditions.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, uneven‐aged forests may improve resilience to drought (Piedallu et al., 2022; Pretzsch et al., 2022). Management could also be adapted to reduce competition within forest stands (Kulha et al., 2023). For example, Sohn et al.…”
Section: Discussionmentioning
confidence: 99%
“…Management could also be adapted to reduce competition within forest stands (Kulha et al, 2023). For example, Sohn et al (2016) observed that heavy thinning improved growth responses following drought in both conifers and broadleaves, although it could be sometimes offset by increased soil water evaporation (Pretzsch et al, 2018).…”
Section: Drought Damage Risk Predictors and Future Forecastingmentioning
confidence: 99%
See 1 more Smart Citation